Electron acceptors for sulphate-reducing bacteria Desulfomicrobium sp. in the process of oxidation of organic compounds - K. V. Sholiak (Біологічні студії, 2013)
In the presence of sulfate in the medium? sulfate-reducing bacteria Desulfomicrobium sp. use it as a final electron acceptor with it’s reduction to hydrogen sulfide. Except sulfate, bacteria Desulfomicrobium sp. are able to use nitrate, сhromate, trivalent iron – Fe (III), fumarate and elemental sulfur as electron acceptors in the process of organic compounds oxidation. Chromate and nitrate provide growth which does not significantly differ from bacterial growth in the medium with sulfate. Under these conditions, Cr+6 is reduced to Cr+3, and nitrates – to nitrite and ammonium. 0.2–2 mM of Cr (III) do not possess any inhibitory effect on the growth of Desulfomicrobium sp. In the presence of sulfate (5 mM) and nitrate (5 mM) in the growth medium, there was observed a simultaneous use of both acceptors of electrons by bacteria. Under the presence of 0.5 mM chromate and 5 mM sulfate in the medium, Cr+6 inhibited sulfate utilization the bacterial cells. Under simultaneous addition of sulphate (5 mM), nitrate (5 mM) and chromate (0.5 mM) into the growth medium, Cr+6 inhibited utilization of sulfate and nitrate by sulfate-reducing bacteria Desulfomicrobium sp.